2015
DOI: 10.1021/acs.jpcb.5b09456
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulations of Anion and Temperature Dependence on Structure and Dynamics of 1-Hexyl-3-methylimidazolium Ionic Liquids

Abstract: In this study, we examine the effect of various anions and temperature on structure and dynamics of 1-hexyl-3-methylimidazolium ionic liquids (ILs) from molecular dynamics simulations. The structural properties show that ILs containing smaller anions like Cl(-) and Br(-) are relatively higher cation-anion interactions, compared to ILs containing larger anions like OTf(-) and NTf2(-). In all ILs, the spatial distribution of anions is closer to the acidic hydrogen atom of the cation compared to the two nonacidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 45 publications
1
29
0
2
Order By: Relevance
“…Recent MD simulations conducted on [C n mim][X], with [X] being different anions, showed that also in the liquid state, the [Tf2N] anion, due to its bulkiness, tends to lay above and below the imidazolium ring, while the [BF 4 ] anion prefers being localised equatorially with respect to the imidazolium ring, in the neighbourhood of the hydrogen atoms. 61,62 These computational observations agree with the mechanism that we are presently indicating to rationalise the experimental evidence.…”
supporting
confidence: 87%
“…Recent MD simulations conducted on [C n mim][X], with [X] being different anions, showed that also in the liquid state, the [Tf2N] anion, due to its bulkiness, tends to lay above and below the imidazolium ring, while the [BF 4 ] anion prefers being localised equatorially with respect to the imidazolium ring, in the neighbourhood of the hydrogen atoms. 61,62 These computational observations agree with the mechanism that we are presently indicating to rationalise the experimental evidence.…”
supporting
confidence: 87%
“…In addition, the diffusive regime can be examined computing the time‐dependent parameter: β(t)=dLn(MSD(t))/dLn(t). When β(t) is close to the unity, the system is in a linear diffusive regime . The extracted β(t) values are shown in Figure S2 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…When b(t) is close to the unity, the system is in a linear diffusive regime. [52] The extracted b(t) values are shown in Figure S2 in the Supporting Information. After approximately 50 ns of simulation time, b(t) values corresponding to the [C 4 PYR] + cations and [Tf 2 N] À anions in all systems fluctuate close to the unity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations